Acute Stress Induces Contrasting Changes in AMPA Receptor Subunit Phosphorylation within the Prefrontal Cortex, Amygdala and Hippocampus - Caudal, Dorian (Public Library of Science, 2010)
Exposure to stress causes differential neural modifications in various limbic regions, namely the prefrontal cortex, hippocampus and amygdala. We investigated whether α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) phosphorylation is involved with these stress effects. Using an acute inescapable stress protocol with rats, we found opposite effects on AMPA receptor phosphorylation in the medial prefrontal cortex (mPFC) and dorsal hippocampus (DH) compared to the amygdala and ventral hippocampus (VH). After stress, the phosphorylation of Ser831-GluA1 was markedly decreased in the mPFC and DH, whereas the phosphorylation of Ser845-GluA1 was increased in the amygdala and VH. Stress also modulated the GluA2 subunit with a decrease in the phosphorylation of both Tyr876-GluA2 and Ser880-GluA2 residues in the amygdala, and an increase in the phosphorylation of Ser880-GluA2 in the mPFC. These results demonstrate that exposure to acute stress causes subunit-specific and region-specific changes in glutamatergic transmission, which likely lead to the reduced synaptic efficacy in the mPFC and DH and augmented activity in the amygdala and VH. In addition, these findings suggest that modifications of glutamate receptor phosphorylation could mediate the disruptive effects of stress on cognition. They also provide a means to reconcile the contrasting effects that stress has on synaptic plasticity in these regions. Taken together, the results provide support for a brain region-oriented approach to therapeutics.